Final answer:
To evaluate the expression Y=3x-5 for x=6, substitute 6 for x, multiply by 3 to get 18, and subtract 5 to obtain the final result Y=13.
Step-by-step explanation:
To evaluate the expression Y=3x-5 when x=6, you simply substitute the value of 6 in for x and then perform the calculation. Here's a step-by-step explanation:
Start with the original equation: Y = 3x - 5.
Substitute x with 6: Y = 3(6) - 5.
Multiply 3 by 6: Y = 18 - 5.
Subtract 5 from 18: Y = 13.
So, the value of Y when x=6 is 13.